Structural health monitoring through surface acoustic wave inspection deployed on capillaries embedded in additively manufactured components - Hinderdael Michaël (EDP Sciences, 2021)
Surface Acoustic Wave inspection is a well-known non-destructive testing technique that receives considerable attention to become implemented as a Structural Health Monitoring system. The current work presents a novel approach to embed Surface Acoustic Wave-based Structural Health Monitoring technology inside additively manufactured components. A capillary network is to be integrated inside the component and Surface Acoustic Wave inspection is then deployed on the free capillary surface during the component’s operation to warn upcoming failures.